Implementation of Self Directed Learning Model Based on Social Challenge to Improve Social Skills of Elementary School Students - Irmaningrum, Rizka Novi; Huda, Mochammad Miftachul; Mudayan, Arfian (Journal of Digital Learning and Education, 2024)
This research aims to describes the application of a self-directed learning model based on social challenges that can improve the social skills of elementary school students. This research uses a qualitative approach, with the type of classroom action research (CAR). The research was conducted collaboratively between researchers and fourth grade teachers. The subjects of the study were 32 fourth grade students of SDN Made 4 Lamongan Regency in the 2024/2025 academic year. The data collection instruments used observation sheets, interviews, tests, and field notes. Data analysis used quantitative descriptive analysis. This research was conducted in two cycles and each cycle consisted of three meetings. The results of the study were that the percentage of students' social skills in cycle I reached 79.50% and in cycle II increased to 85.4%. Based on the results of this study, it can be concluded that the increase in students' social skills occurred due to the implementation of the self-directed learning approach based on social challenges.